2017
DOI: 10.1021/acs.jpcc.6b11959
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Nanoscale Oxygen-Ion Intercalation into Epitaxial MoO2 Thin Films

Abstract: In transition metal oxides (TMOs), lots of physical phenomena such as metal–insulator transitions (MIT), magnetism, and ferroelectricity are closely related to the amounts of oxygen contents. Thus, understanding surface oxidation process in TMOs and its effect are important for enhancing performances of modern electronic and electrochemical devices due to miniaturization of those devices. In this regard, MoO2+x (0 ≤ x ≤ 1) is an interesting TMO, which shows MIT driven by the change of its oxygen content, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Subsequently, oxygen can react at the vacancy sites with Mo and occupy all vacancies in the inner layers. Thermal annealing in gas ambient at low pressure are frequently employed to facilitate intercalation of small gas molecules such as oxygen [ 31 ] and hydrogen [ 32 ] in 2D materials. Importantly, it should be very cautious that annealing only causes intercalation of oxygen in MoTe 2 without oxidizing it.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, oxygen can react at the vacancy sites with Mo and occupy all vacancies in the inner layers. Thermal annealing in gas ambient at low pressure are frequently employed to facilitate intercalation of small gas molecules such as oxygen [ 31 ] and hydrogen [ 32 ] in 2D materials. Importantly, it should be very cautious that annealing only causes intercalation of oxygen in MoTe 2 without oxidizing it.…”
Section: Resultsmentioning
confidence: 99%
“…This comparative experiment indicated that annealing in air may oxidize metallic SrMoO 3 into insulating SrMoO 4 above 450 °C, which was a considerably higher temperature than the 250 °C reported for oxygen intercalation from MoO 2 to MoO 3 films. [ 41 ] We propose that the oxygen diffusion barrier could preserve the properties of SrMoO 3 at high temperatures, as demonstrated by a six‐unit‐cell Ba 0.5 Sr 0.5 TiO 3 capping layer. [ 42 ] The thermal stability of correlated perovskite TCs is sufficient for most applications working below 400 °C, including military weapons, invisible circuitry, smart windows, infrared sensors, and transparent solar cells.…”
Section: Thermal Stability Of Srmoo3 Epitaxial Films On Al2o3mentioning
confidence: 99%
“…MoO 2 thin films can be fabricated using a molybdenum target using spin coating, pulsed laser deposition, reactive sputtering, and thermal evaporation [18]. In the case of the sputtering process, to optimize the performances of the thin film, most researchers have studied the influences of sputtering parameters on the film properties, including the type of sputter power (radio-frequency (RF) magnetron reactive sputtering, direct current (DC) magnetron reactive sputtering), working pressure (oxygen partial pressure from 1.00 × 10 −3 mbar to 1.37 × 10 −3 mbar), base pressure, atmosphere (Ar-O 2 sputtering gas), sputter powder (electrical conductivity varying from 1.6 × 10 −5 S/cm to 3.22 S/cm), film thickness, and post-annealing treatment (oxygen annealing range from 250 to 350 • C) [19][20][21][22][23]. However, it is difficult to elucidate how the target influences the properties of various films, the sputtering process, and the correlations between film properties and target performance have not been well established.…”
Section: Introductionmentioning
confidence: 99%